Drinking from graveyard wells : stories - Ndlovu, Yvette Lisa (The University Press of Kentucky, 2023)
"'Even in death, who has ownership over Black women's bodies?' Questions like this lurk between the lines of this stunning collection of stories that engage with African women's histories, both personal and generational. Their history is not just one thing: there is heartbreak and pain, and joy, and flying and magic, so much magic. An avenging spirit takes on the patriarchy from beyond the grave. An immigrant woman undergoes a naturalization ceremony in an imagined American state that demands that immigrants pay a toll of the thing they love the most. A first-generation Zimbabwean-American woman haunted by generational trauma is willing to pay the ultimate price to take her pain away-giving up her memories. A neighborhood gossip wakes up to find that houses are mysteriously vanishing in the night. A shapeshifting freedom fighter leaves a legacy of resistance to her granddaughter. In Drinking from Graveyard Wells, Yvette Lisa Ndlovu assembles poignantly reflective stories that center the voices of African women charting their own Black history through the ages. Ndlovu's stories play with genre, from softly surreal to deeply fantastical. Each narrative is wrapped in the literary eloquence and tradition of southern African mythology, transporting readers into the lives of African women who have fought across space and time to be seen. Drawing on her own early experiences as a Zimbabwean living under the Mugabe dictatorship, Ndlovu's stories are grounded in truth and empathy. Ndlovu boldly offers up alternative interpretations of a past and a present that speculates upon the everyday lives of a people disregarded. Her words explore the erasure of African women while highlighting their beauty and limitless magic. Immersed in worlds both fantastical and familiar, readers find themselves walking alongside these women, grieving their pain, and celebrating their joy, all against the textured backdrop of Zimbabwe"--